Interactions between Borrelia burgdorferi and its hosts across the enzootic cycle. (11th January 2021) - Helble, Jennifer D.; McCarthy, Julie E.; Hu, Linden T.
Abstract: The bacterial pathogen Borrelia burgdorferi is the causative agent of Lyme disease and is transmitted to humans through an Ixodes tick vector. B. burgdorferi is able to survive in both mammalian and tick hosts through careful modulation of its gene expression. This allows B. burgdorferi to adapt to the environmental and nutritional changes that occur when it is transmitted between the two hosts. Distinct interactions between the spirochete and its host occur at every step of the enzootic cycle and dictate the ability of the spirochete to survive until the next stage of the cycle. Studying the interface between B. burgdorferi, the Ixodes tick vector and the natural mammalian reservoirs has been made significantly more feasible through the complete genome sequences of the organisms and the advent of high throughput screening technologies. Ultimately, a thorough investigation of the interplay between the two domains (and two phyla within one domain) is necessary in order to completely understand how the pathogen is transmitted.